2021
DOI: 10.1186/s12904-021-00862-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of dying in hospital general wards: a cross-sectional study about the end-of-life care

Abstract: Background In the last decade, access to national palliative care programs have improved, however a large proportion of patients continued to die in hospital, particularly within internal medicine wards. Objectives To describe treatments, symptoms and clinical management of adult patients at the end of their life and explore whether these differ according to expectation of death. Methods Single-centre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
1
2
0
1
Order By: Relevance
“…However, the study also revealed that RNs' cultural, religious, educational and/or ethnic backgrounds may influence end‐of‐life nursing practices (Rittle, 2015 ). This is consistent with existing literature that highlights how cultural norms and education play a crucial role in shaping RNs' beliefs about death and dying and influence the provision of care (Binda et al, 2021 ; Juranić et al, 2023 ). These findings highlight the need to examine these factors to develop recommendations for improving end‐of‐life care practices in Saudi Arabia and internationally.…”
Section: Discussionsupporting
confidence: 91%
“…However, the study also revealed that RNs' cultural, religious, educational and/or ethnic backgrounds may influence end‐of‐life nursing practices (Rittle, 2015 ). This is consistent with existing literature that highlights how cultural norms and education play a crucial role in shaping RNs' beliefs about death and dying and influence the provision of care (Binda et al, 2021 ; Juranić et al, 2023 ). These findings highlight the need to examine these factors to develop recommendations for improving end‐of‐life care practices in Saudi Arabia and internationally.…”
Section: Discussionsupporting
confidence: 91%
“…Family members should be allowed to think about the transfer decision. Clinicians may remind family members that terminally ill, older adult patients who remain in the general ward usually cannot receive adequate physical and psychospiritual care (Binda et al, 2021; Sato et al, 2008). The hospice ward has specialist staff and a thoughtful environment that not only effectively improves the patient’s quality of life but also reduces the burden on caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Based on reviews of people dying with dementia and cancer, many may experience pain (12%-96%), difficulty breathing (8%-83%), fatigue (22%-93%), incontinence (32%-65%), and anxiety (6%-57%) [ 2 , 6 ]. Studies in intensive care units (ICU), hospital general wards, nursing homes, and among the general public reported similar percentages of these symptoms, with the addition of agitation (12%—71%) [ 4 , 5 , 7 ], sleep disturbances (18%—56%) [ 7 , 8 ], nausea (9%—59%) [ 4 , 8 ], delirium (75%—91%) [ 3 , 9 , 10 ], fever (16%—61%), and [ 4 , 8 ] pressure sores (16%—42%) [ 3 , 4 ]. To relieve health-related suffering at the end of life, which is a core task of palliative care [ 11 ], it is essential to identify these distressing symptoms in a timely manner.…”
Section: Introductionmentioning
confidence: 99%